Cochrane corner: water for wound cleansing. - Henton, J; Jain, A (2012)
BACKGROUND: Although various solutions have been recommended for cleansing wounds, normal saline is favoured as it is an isotonic solution and does not interfere with the normal healing process. Tap water is commonly used in the community for cleansing wounds because it is easily accessible, efficient and cost effective; however, there is an unresolved debate about its use. OBJECTIVES: The objective of this review was to assess the effects of water compared with other solutions for wound cleansing. SEARCH STRATEGY: For this update we searched the Cochrane Wounds Group Specialised Register (Searched 22 February 2010); The Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, 2010 Issue 1); Ovid MEDLINE - 2007 to February Week 2 2010; Ovid MEDLINE - In-Process and Other Non-Indexed Citations (Searched19 February 2010); Ovid EMBASE - 2007 to 2010 Week 06; EBSCO CINAHL - 2007 to 22 February 2010. SELECTION CRITERIA: Randomized and quasi-randomized controlled trials that compared the use of water with other solutions for wound cleansing were eligible for inclusion. Additional criteria were outcomes that included objective or subjective measures of wound infection or healing. DATA COLLECTION AND ANALYSIS: Two review authors independently carried out trial selection, data extraction and quality assessment. We settled differences in opinion by discussion. We pooled some data using a random-effects model.